Predicting length of stay in head and neck patients who undergo free flap reconstruction. Issue 3 (28th May 2020) - Lindeborg, Michael M.; Sethi, Rosh K. V.; Puram, Sidharth V.; Parikh, Anuraag; Yarlagadda, Bharat; Varvares, Mark; Emerick, Kevin; Lin, Derrick; Durand, Marlene L.; Deschler, Daniel G.
Abstract: Objective: Understanding factors that affect postoperative length of stay (LOS) may improve patient recovery, hasten postoperative discharge, and minimize institutional costs. This study sought to (a) describe LOS among head and neck patients undergoing free flap reconstruction and (b) identify factors that predict increased LOS. Methods: A retrospective cohort was performed of 282 head and neck patients with free flap reconstruction for oncologic resection between 2011 and 2013 at a tertiary academic medical center. Patient demographics, tumor characteristics, and surgical and infectious complications were characterized. Multivariable regression identified predictors of increased LOS. Results: A total of 282 patients were included. Mean age was 64.7 years (SD = 12.2) and 40% were female. Most tumors were located in the oral cavity (53.9% of patients), and most patients underwent radial forearm free flap (RFFF) reconstruction (RFFF—73.8%, anterolateral thigh flap—11.3%, and fibula free flap—14.9%). Intraoperative complications were rare. The most common postoperative complications included nonwound infection (pneumonia [PNA] or urinary tract infection [UTI]) (15.6%) and wound breakdown/fistula (15.2%). Mean and median LOS were 13 days (SD = 7.7) and 10 days (interquartile range = 7), respectively. Statistically significant predictors of increased LOS included flap take back (Beta coefficient [ C ] = +4.26, P  < .0001), in‐hospital PNA or UTI ( C = +2.52, P = .037), wound breakdown or fistula ( C = +5.0, P  < .0001), surgical site infection ( C = +3.54, P = .017), and prior radiation therapy ( C = +2.59, P = .004). Conclusion: Several perioperative factors are associated with increased LOS. These findings may help with perioperative planning, including the need for vigilant wound care, optimization of antibiotics prophylaxis, and institution‐level protocols for postoperative care and disposition of free flap patients. Level of Evidence: 2b; retrospective cohort. Abstract :